Rural-urban differential in maternal mortality estimate in Nigeria, sub-Saharan Africa (2010)
In developing countries, the traditional sources of demographic statistics in which the estimates of demographic indices are based are either non-existence or incomplete. Data requirements on maternal deaths are always very large and costly. The indirect method (sisterhood method) for estimating maternal deaths was designed primarily as check to these problems. The study used Nigeria Demographic and Health Survey (NDHS), 2008 data. A total of 18,250 (6,894 urban and 11,356 rural) adults responded to questions essential for the estimation of maternal mortality. The P/F ratio method was used to adjust the total fertility rates (TFR) in urban and rural areas. Thereafter, the life-time risks of maternal deaths (LTRMD) were estimated for the two areas. These were later converted to maternal mortality ratio (MMR). Data analyses revealed that the adjusted total fertility rates for urban and rural areas were 5.26 and 7.12 respectively. The LTRMD in urban was 0.0221 (1 in 45) whereas, in rural area it was 0.0309 (1 in 32). These results correspond to MMR of 424/100,000 and 440/100,000 live births in urban and rural areas respectfully. These are not far from the national estimate of 436/100,000 live births as evidence in this study. This method provided a robust estimate of MMR in both urban and rural areas and shows that the MMR in Nigeria is reducing. However, the figures at the two locations are still high. Government and international agencies should put appropriate mechanisms in place for further reduction in the prevalence.